Cuantificación de metales pesados (Pb, As, Cd, Hg) en las hojas de Tessaria integrifolia procedente del distrito de Moche-Trujillo- La Libertad - Castillo Rodríguez, Evelyn Karito (2017)
The objective of this study was to quantify the heavy metals (Pb, As, Cd, Hg) in the leaves of Tessaria Integrifolia from the district of Moche-Trujillo-Libertad. The leaves of the species under study were collected on the banks of the Moche River in the city of Trujillo during the month of May 2017 and later it was identified in the herbarium Truxillenses (HUT) of the National University of Trujillo. The dried leaves were milled, sieved and stored in amber jars for the corresponding study. The samples were processed by acid digestion and subsequently read in the atomic absorption spectrophotometer. In the study of the quantification of heavy metals in the sheet of Integrifolia the concentrations of each metal were expressed in mg / kg, both dry weight and fresh weight, which allowed us to compare these values with the references given in different bibliographies ( WHO, European Pharmacopoeia, Cuban Standard). The results obtained were; The lead concentration (Pb) is 8.397 mg / kg; Cadmium (Cd) 0.645mg / kg; Mercury (Hg) 0.304mg / kg and arsenic (As) 1.267 on a dry basis. The concentrations of lead (Pb) 2.022mg / kg; Cadmium (Cd) 0.155mg / kg; Mercury (Hg) 0.073 mg / kg and arsenic (As) 0.308 on a wet basis